Influence of Different Phases of Resistance Training on Selected Psychological Variables of Kabaddi Players - Dr.Sudhakara Babu Mande, Dr. P Suryachandra Rao (International journal of economic perspectives, 2022)
The aim of this study is to find out the effect of changes during different phases of training on psychological variables, anxiety and achievement motivation of kabaddi players. 30 Kabaddi players who represented their colleges at inter collegiate level competitions were selected and given resistance training under different phases, conditioning, intensive, in-season, and off season by manipulating the load, intensities and frequencies of selected weight training exercises. Psychological variables anxiety and achievement motivation were measured through standard questionnaires prior to different phases and training which formed the initial scores and immediately after each season of resistance training phases. The collected data on selected psychological variables anxiety and achievement motivation was statistically analysed using Repeated Measures of ANOVA. Results proved that different phases of training altered anxiety and there were significant differences between initial and in-season phase. Similarly different phases of training improved achievement motivation and there was significant difference between initial scores and in season training. It was concluded that the different phases of training can be utilized for stabilizing competition anxiety and achievement motiaiton of kabaddi platyers.